SPECIFIC FEATURES OF THE USE OF MEDIATION IN DISPUTES REGARDING THE PROVISION OF MAINTENANCE TO PARENTS - Usmonova Mahliyo Sobirjon qizi (Bright Mind Publishing, 2025)
In world practice, family mediation is one of the first and most widespread types of mediation. The current legislation of Uzbekistan has introduced a number of procedures for resolving disputes. This is due to the fact that in recent years, in the practice of law enforcement, the parties have been preferring to use the most alternative methods of resolving legal disputes. In our opinion, one of the most acceptable methods of resolving legal disputes before trial is the institution of mediation, which does not bypass family relations.